2018
DOI: 10.1002/tesq.463
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of International Accents and Shared First Language on Listening Comprehension Tests

Abstract: This study examines the effect of incorporating a variety of international English accents into a simulated TOEFL listening comprehension test in growing recognition of internationalization of language teaching and learning in the field of TESOL. Although some highstakes English proficiency exams have begun incorporating speech samples produced by speakers from a range of inner circle Englishspeaking backgrounds (e.g., Britain, the United States, Australia), the inclusion of samples produced by speakers of out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 35 publications
9
58
0
Order By: Relevance
“…For example, Major et al [12] argued that Chinese and Japanese listeners had a relatively decent understanding of Spanish-accented English due to the shared prosodic features that existed among Chinese, Japanese, and Spanish. Other studies reported that Japanese L1 listeners found Japanese L1 speakers of English were more intelligible than native English listeners found them to be [13], and also Indian and South African listeners were able to comprehend listening passages recorded by their own shared L1 speakers, respectively [14].…”
Section: Listener Background 21 Listener First Language Statusmentioning
confidence: 98%
“…For example, Major et al [12] argued that Chinese and Japanese listeners had a relatively decent understanding of Spanish-accented English due to the shared prosodic features that existed among Chinese, Japanese, and Spanish. Other studies reported that Japanese L1 listeners found Japanese L1 speakers of English were more intelligible than native English listeners found them to be [13], and also Indian and South African listeners were able to comprehend listening passages recorded by their own shared L1 speakers, respectively [14].…”
Section: Listener Background 21 Listener First Language Statusmentioning
confidence: 98%
“…With the diversity of accents that English speakers are exposed to in the TLU domain for which many listening tests are designed (Taylor and Geranpayeh, 2011), L2 listening assessment has been argued to reveal the changing demographics in English speaking contexts (Ockey and French, 2014) by incorporating accented speech. For example, inner and outer circle English accents have been used in high-stakes listening tests, including the TOEFL iBT, Test of English for International Communication (TOEIC), and IELTS (Kang et al, 2019). However, concerns about the inclusion of non-standard accents have been raised.…”
Section: Speakersmentioning
confidence: 99%
“…Empirical evidence provided partial support for a shared-L1 advantage phenomenon (Major et al, 2002;Harding, 2012;Dai and Roever, 2019;Kang, et al, 2019). Major et al (2002) found that Spanish-L1 test takers scored higher when listening to Spanish-accented speech, but Chinese-L1 test takers performed worse when listening to Chinese-accented speech.…”
Section: Speakersmentioning
confidence: 99%
“…However, L2 teachers and practitioners have left unsupported on how to include such multiple varieties of accents in their own classrooms (Sung, 2016). As far as L2 listening research is concerned, the effect of accent on listening comprehension has received research attention recently (Kang, Thomson, & Moran, 2019). Within this line of enquiry, it is argued that the type of accent and accented speech affects the degree of listening comprehension (Rubin, 1992).…”
Section: Statement Of Problemmentioning
confidence: 99%
“…The findings revealed that although students showed more preference to native teachers, there was no significant difference between learners' ratings of comprehensibility for both native and non-native teachers. In another study, Kang, Thomson, and Moran (2019) investigated the impact of including different varieties of English accents in a listening section of a mock test of English as a foreign language (TOEFL) test on leaners' degree of comprehensibility. In so doing, speakers of six distinct English varieties were employed to produce speech samples for the listening test.…”
Section: Review Of the Literaturementioning
confidence: 99%